2020
DOI: 10.1177/1352458520929192
|View full text |Cite
|
Sign up to set email alerts
|

Critical spinal cord lesions associate with secondary progressive motor impairment in long-standing MS: A population-based case-control study

Abstract: Background: Progressive motor impairment anatomically attributable to prominent, focally atrophic lateral column spinal cord lesions (“critical lesions”) can be seen in multiple sclerosis (MS), for example, progressive hemiparetic MS. Objective: The aim of this study was to investigate whether similar spinal cord lesions are more frequent in long-standing MS patients with secondary progressive motor impairment (secondary progressive MS (SPMS)) versus those maintaining a relapsing-remitting course (relapsing-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…This is compatible with an MRI study investigating the cervical cord ( Kearney et al, 2015a ) and histological studies as SC lesions primarily reflect demyelination ( Nijeholt et al, 2001 ), whereas the underlying cause of SC atrophy is less clear ( Evangelou et al, 2005 , Petrova et al, 2018 ). On the other hand, studies exist that reported a more direct relation between SC lesions and atrophy ( Pravatà et al, 2019 , Sechi et al, 2021 ). Further, simply because both measures develop over time, as underlined by the high correlation with disease duration, we expected at least some degree of correlation.…”
Section: Discussionmentioning
confidence: 99%
“…This is compatible with an MRI study investigating the cervical cord ( Kearney et al, 2015a ) and histological studies as SC lesions primarily reflect demyelination ( Nijeholt et al, 2001 ), whereas the underlying cause of SC atrophy is less clear ( Evangelou et al, 2005 , Petrova et al, 2018 ). On the other hand, studies exist that reported a more direct relation between SC lesions and atrophy ( Pravatà et al, 2019 , Sechi et al, 2021 ). Further, simply because both measures develop over time, as underlined by the high correlation with disease duration, we expected at least some degree of correlation.…”
Section: Discussionmentioning
confidence: 99%
“…While the murine EAE model does not have significant brain lesions, it causes demyelinating SC lesions with some animals developing hind-limb paralysis. The spinal cord is disproportionately affected in patients with progressive MS [ 39 ] and those with lateral cord lesions [ 40 ] and focal atrophy, termed “critical” [ 41 ], are due to axonal loss within the corticospinal tract leading to paraparesis. Our results show comparable T cell infiltration, demyelination, and axonal loss in SC white matter and optic nerve during peak of EAE (15 dpi), which was accompanied by a functional delay in VEPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, cervical spinal cord involvement is also associated with marked brain cortical atrophy and in a reduction of the pyramidal and cerebellar tracts, which could further accelerate the neurodegenerative process ( 11 ). In fact, some observations provide strong evidence that SC injury, rather than diffuse symmetric injury to the brain's white matter, is the major contributor to motor progression in MS ( 12 ).…”
Section: Discussionmentioning
confidence: 99%